The impact of the use of the intranet network on the sharing of knowledge in the economic enterprise - a case study of the LafargeHolcim Cement Production Corporation - M’sila - - Benelbar, Moussa; Attallah, Yacine; CHerrid, Amar (Milev Journal of Research and Studies, 2021)
This research aims to study the role of the Intranet in the sharing of knowledge in the production of cement Lafarge Holcim-M'sila - Algeria. The main concepts related to the intranet and its uses in the organization were discussed and shared knowledge, objectives and obstacles. The descriptive approach was used and the survey was used as a basic tool for obtaining information and using a number of statistical methods to test the hypothesis of the study and analyze its results. A very low correlation was found between Intranet usage and the process of knowledge sharing by respondents, as well as the absence of an impact on the use of the Intranet to share the knowledge of the institution under study.